Spectrometric Determination of Heavy Metals Present in Mango Fruit of Nepali Origin - Pant, Naresh; Subedee, Anup; Gharti, Ram Bahadur; Shrestha, Santu (Amrit Research Journal, 2020)
Quantitative determination of heavy metals; Fe, Zn, Co, Pb and Ni in Mango fruit of Nepali origin, locally sourced was carried out. Fifteen Mango samples were collected by random sampling method, converted into analyte sample by standard method and analyzed by using Atomic absorption spectrometric method. The amount of heavy metals Fe, Zn, Co and Ni present in sample was, 0.570±0.48, 0.510±0.031, 0.431±0.021, 0.106±0.003 mg/kg respectively. The results indicated the concentration of Zn & Co were higher (WHO 0.320 & 0.05), and the concentration of Nickel (Ni) was below the maximum permissible limit issued by WHO. The concentration of the Lead (Pb) was found below the detection limit of the instrument used.